Board Attributes and Tax Planning of Corporate Organisations in Nigeria - Imuetinyan EGUAVOEN; Isaac UKARIN; Ojuye Thomas ENEWEROME (Management and Economics Review, 2023)
This study investigated board attributes and tax planning of corporate organisations in Nigeria. Different variables of board attributes (board independence BIND)), board size (BSIZ), and gender diversity (GDIV) were critically analysed so as to establish their relationship with tax planning (TAXP). For the aim of this very paper to be accomplished, eighty-five (85) non-financial companies that are found to be quoted on Nigerian Stock Exchange (NSE) were cautiously picked and carefully analyzed for the particular period of 2016 to 2020. Panel least squares regression was used with the help of econometric packages (Eview 9.0) to analyse that data. The result indicated that the explanatory variable of board independence BIND was negatively and insignificantly related to tax planning (TAXP), while board size (BSIZ) and gender diversity (GDIV) were positively and significantly related to tax planning (TAXP). Therefore, due to the significant relationship which exists between the board size (BSIZ) and gender diversity (GDIV) with tax planning (TAXP), the need to properly investigate the issues cannot be over-stressed. Therefore, it is recommended that board size (BSIZ) and gender diversity (GDIV) should be given substantial attention when studying board attributes in relation to tax planning of Nigerian companies; precisely.